On Rate of Return Measurement in Education - Dziechciarz, Józef (O pomiarze stopy zwrotu z inwestycji w edukację, 2011)
The traditional, Humboldtian type of the university faces serious criticism. The answer of the European Commission to weaknesses is the Modernization concept with a goal of transformation from Humboldtian towards Entrepreneurial University. Modernization concept is the policy promoting three main reforms. Curricular reform symbolized by the Bologna Process is accompanied by the governance reform and the funding reform designed to enable change from inputoriented towards output-oriented budgeting. The discussion of concept and some possible solutions in measurement of the efficiency and effectiveness in the education system is given. Special attention is concentrated on rate of return measurement in education, particularly in tertiary education.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 49-66
Keywords: Deklaracja bolońska; stopa zwrotu; szkolnictwo wyższe; Bologna process; rate of return; higher education